2014
DOI: 10.1111/aogs.12404
|View full text |Cite
|
Sign up to set email alerts
|

Infertility experience and health differentials – a population‐based comparative study on infertile and non‐infertile women (the HUNT Study)

Abstract: The study confirms the adverse effect of infertility on health and life-satisfaction. The childless infertile women stand out as being vulnerable to the detrimental consequences of infertility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 27 publications
1
17
1
Order By: Relevance
“…A study conducted in Sweden (n = 520) showed that women who underwent IVF therapy in the past had a higher risk of depression after 20-23 years, regardless of whether they gave birth in the meantime or remained childless [25]. A different study by Roastad et al (n = 9200) on the Norwegian population did not reveal significant differences in the incidence of depression among infertile women compared to those without infertility problems and in infertile women who were childless compared to those with children [24]. Another study on depression among couples undergoing ART treatment (n = 98) showed that couples undergoing subsequent ART cycles presented a higher level of depressive symptoms compared to couples beginning ART therapy for the first time.…”
Section: The Influence Of Infertility and Art On Depressionmentioning
confidence: 95%
See 1 more Smart Citation
“…A study conducted in Sweden (n = 520) showed that women who underwent IVF therapy in the past had a higher risk of depression after 20-23 years, regardless of whether they gave birth in the meantime or remained childless [25]. A different study by Roastad et al (n = 9200) on the Norwegian population did not reveal significant differences in the incidence of depression among infertile women compared to those without infertility problems and in infertile women who were childless compared to those with children [24]. Another study on depression among couples undergoing ART treatment (n = 98) showed that couples undergoing subsequent ART cycles presented a higher level of depressive symptoms compared to couples beginning ART therapy for the first time.…”
Section: The Influence Of Infertility and Art On Depressionmentioning
confidence: 95%
“…Another study conducted in Norway on a group of 9200 women evaluated self-reported health, functional impairment, the presence of anxiety and depression and the quality of life in a group of infertile women compared to women without infertility problems and among infertile women with or without a child. Childless infertile women reported more health-related complaints and a lower life satisfaction, yet there were no significant differences in the level of anxiety compared to women with a child, either with or without a history of infertility [24]. Authors of a different study on a group of 530 women in Sweden evaluated long-term effects of IVF procedure on the mental state.…”
Section: The Influence Of Infertility and Art Procedures On Anxietymentioning
confidence: 99%
“…Besides a reproductive system disease, infertility is also a biopsychosocial health problem in the sense that both causation and outcome are product of an interaction between biological, psychosocial and social factors (Leigh & Reiser, 1980). Research has shown that experiencing infertility and its treatments can decrease quality of life (Fekkes et al, 2003;Lau, Wang, Kim, Yang & Tsui, 2008;Onat & Beji, 2012) and increase distress (Verhaak et al, 2007;Rostad, Schmidt, Sundby & Schei , 2014). Indeed, couples report the experience of infertility as one of the most stressful events in their lives (Klonoff-Cohen, Chu, Natarajan & Sieber, 2001).…”
Section: Effects Of Life Events On Infertility Diagnosis: Comparison mentioning
confidence: 99%
“…Infertility remains a threat to successful reproduction by couples desirous of pregnancy [1,2]. Its problems are multidimensional and can impose profound physical, psychological and social strains on both partners in a couple [1][2][3][4]. The childless infertile women stand out as being vulnerable to the detrimental consequences of infertility [4].…”
Section: Introductionmentioning
confidence: 99%